REQUEST REALIZATIONS OF INDONESIAN ESP LECTURERS - Arif Nugroho (University of Muhammadiyah Malang, 2019)
Drawing on the Speech Act theory, the present study endeavored to delineate the most frequently used request strategies by Indonesian English for Specific Purposes lecturers. In addition, it examined the involvement of situational variables of social distance, power, and imposition on the choice of their strategies. Another objective has been to reveal the reasons why the lecturers choose such strategies. To this end, a descriptive approach was adopted by employing Discourse Completion Test questionnaire and semi-structured interview to gather the data fromtwenty-eightESP lectures teaching at some different departments who werepurposively selected as the participants in this study. The results of the questionnaire illustrated that the participants made use of conventionally indirect expressions (81.2%) for requests more frequently than other strategies. The semi-structured interview figured out that the participants’ reason of utilizing conventionally indirect strategy was due to the cultural factors. Moreover, the situational variables of social distance, power, and imposition slightly affected the participants’ choice of requests, but they had some influences on determining the degree of politeness. Furthermore, the analyzed data revealed the fact that first language culture, urgency of the requests, and physical attractiveness also influenced the participants’ choice of request strategies.